The Effects of Workplace Well-Being and Calling on Work Engagement Among Nurses - Komang Genta Ayu Saraswati; Aries Yulianto (Poltanesa, 2026)
Nurses frequently work under high job demands, emotional pressure, rotating shifts, and direct responsibility for patient safety. These conditions make work engagement an important issue because engaged nurses are more likely to maintain energy, dedication, and focus during patient care. This study examined the predictive effects of workplace well-being and calling on work engagement among nurses. A quantitative cross-sectional design was used with 428 nurses who were actively working and had worked for at least one year in their current workplace. Data were collected from February to April 2026 through online and direct questionnaires. Work engagement was measured using the Utrecht Work Engagement Scale-9, workplace well-being using the Workplace Well-being Index, and calling using the CVQ. Multiple linear regression showed that workplace well-being positively predicted work engagement (b = 0.110, β = 0.438, t = 10.603, p < 0.001), and calling also positively predicted work engagement (b = 0.052, β = 0.157, t = 3.796, p < 0.001). The model explained 28.0% of work engagement variance (R² = 0.280, F = 55.08, p < 0.001). These findings indicate that external workplace resources and personal meaning are associated with nurses’ work engagement. Because the study used a cross-sectional design, the findings should be interpreted as predictive associations rather than causal effects.